Performing Quality Assurance of Carbon Dioxide for Carbon Capture and Storage - Arul Murugan; Richard J. C. Brown; Robbie Wilmot; Delwar Hussain; Sam Bartlett; Paul J. Brewer; David R. Worton; Thomas Bacquart; Tom Gardiner; Rod A. Robinson; Andrew J. Finlayson (C, 2020)
Impurities in carbon dioxide can affect several aspects of the carbon capture and storage process, including storage capacity, rock erosion, accuracy of flow meters, and toxicity of potential leaks. There is an industry need for guidance on performing purity analysis before carbon dioxide is transported and stored. This paper reviews selected reports that specifically provide threshold amount fraction limits for impurities in carbon dioxide for the purpose of transport and storage, with rationales for these limits. A carbon dioxide purity specification is provided (including threshold amount fractions of impurities) on the basis of the findings, as well as recommendations on further work required to develop a suitable gas metrology infrastructure to support these measurements including primary reference materials, sampling methods, and instruments for performing purity analysis. These recommendations provide important guidance to operators and gas analysis laboratories for performing quality assurance.